Training on The Utilization of Mendeley and Similarity in Increasing The Quality of Students’ Academic Work - Ayuni, Rossa; Meirani, Meirani (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
Undergraduate students (S1) who complete their studies are required to be able to write not only a final project in the form of a thesis, but also a scientific pa-per in the form of scientific articles. However, the issue is that students view writing research reports as a very tiresome task, whether it's making quota-tions, creating lists, or many prefer a fast flow such as copy paste. As a result, this training activity is predicted to be beneficial for students in terms of writ-ing research results and the outcomes of their studies in the form of scientific papers, as well as enhancing the quality of scientific articles for students, par-ticularly in the field of education. The instructional approach is a combination of lecture, question and answer, simulation, and practice.